Design Of Bipa Teaching Materials Based On Folklore In The Indonesian Language For Foreign Speakers Learning Resources And Media Course - Isti Asrifah; Supriyadi Supriyadi; Salam Salam (Universitas Negeri Gorontalo, 2022)
The design of Indonesian language for foreign speakers (BIPA) teaching materials based on Gorontalo folklore has considerable potential to help preserve Gorontalo culture. This study aims to describe the needs for BIPA teaching materials based on Gorontalo folklore, the implementation design of BIPA teaching materials based on Gorontalo folklore, and the feasibility of implementing BIPA teaching materials based on Gorontalo folklore in the BIPA Learning Resources and Media course. This development research involved teaching materials used in learning BIPA resources and media obtained by observation, surveys, and documentation of BIPA majoring students in the department of letters and culture, faculty of letters and culture, UNG, and collected for three months. Those data were further analyzed using qualitative techniques with three stages: data reduction, data presentation, and conclusions/data verification. The results show that the level of need for teaching materials is very high. It can be seen from the results obtained that the overall average for students is 4.5%, and for lecturers/material experts, it is 4.8%. In addition, this study also assessed the teaching materials used previously as a reference in compiling teaching materials that suit their needs. For students, the results are 4.1%, and for lecturers/material experts, it is 3.9%, indicating the need for renewal of teaching materials to improve learning. The implementation design was designed by explaining all the primary learning materials obtained through the description of the RPS (Semester Learning Plan). Each media was given an example of an implementation using Gorontalo folklore. The last is the feasibility assessment given to teaching lecturers/material experts for the BIPA Learning Resources and Media subject, showing an average result of 4.5%. All in all, this study concludes that the teaching material entitled